Early cardiovascular risk and all‐cause mortality following an incident of severe hypoglycaemia: A population‐based cohort study. Issue 8 (9th May 2019) - Lo, Shih‐Chang; Yang, Yi‐Sun; Kornelius, Edy; Huang, Jing‐Yang; Lai, Yung‐Rung; Huang, Chien‐Ning; Chiou, Jeng‐Yuan
Abstract: Aims: Severe hypoglycaemia is associated with a high risk of cardiovascular events in patient with diabetes. The aim of this study was to clarify the temporal relationship between hypoglycaemia and cardiovascular events. Materials and methods: This observational cohort study was conducted using Taiwan's Longitudinal Cohort of Diabetes Patients Database, which included 360 000 patients with newly diagnosed diabetes during the period 1999 to 2001. Patients with the first severe hypoglycaemia after 2002 served as the study cohort. Each patient in the study cohort was matched with two control patients without severe hypoglycaemia, based on a propensity score. A joinpoint regression model was used to determine trends in all‐cause mortality and incidence of cardiovascular disease (CVD) events in both cohorts. Results: A total of 10 157 patients with severe hypoglycaemia and 20 314 matched controls were recruited. Patients with severe hypoglycaemia had a significantly higher risk of CVD (HR, 7.28; 95% CI, 5.19–10.20) and all‐cause mortality (HR, 19.92; 95% CI, 13.42–29.56) during the first month compared with those without. In patients with severe hypoglycaemia, the incidence of CVDs dropped by 17.29% monthly during the first 4 months and slowly decreased (−0.67%) during subsequent months. All‐cause mortality decreased by 16.55% and 3.24% monthly during months 0–6 and months 6–17, respectively. Conclusions: Severe hypoglycaemia is associated with a greater risk of cardiovascular events and death, especially during the first month following a hypoglycaemic episode. Patients prone to severe hypoglycaemia should be made aware of the elevated risk of subsequent cardiovascular events.